PENGARUH PEMBERIAN PAKAN KOMPLIT FERMENTASI BERBASIS SERASAH GAMAL DAN BATANG PISANG DENGAN IMBANGAN YANG BERBEDA TERHADAP TINGKAH LAKU MAKAN KAMBING KACANG (Effects of feeding fermented complete feeds differing in the ratio between gliricidia.....) - S. E. Manehat; I Gusti Ngurah Jelantik; I. Benu (Universitas Nusa Cendana, 2020)
The objective of this experiment was to determine the effect of feeding complete feeds differing in the ratio between gliricidia fallen leaf and banana pesudostem on feeding behaviour of Kacang goats. This experiment followed a 4x4 latin square design with four treatments, i.e. P0S70: 70% gliricidia fallen leaf and 30% concentrate, P30S40: 40% gliricidia fallen leaf, 30% banana pseudostem and 30% concentrate, P40S30: 30% gliricidia fallen leaf, 40% banana pseudostem and 30% concentrate, and P70S0: 70% banana pseudostem and 30 concentrate. The measured variables included the frequency and eating time, frequency and ruminating time, and frequency and resting time. Data were subjected to Analyses of Variance (ANOVA) followed by Duncan Multiple Range Test to separate between means. Results showed that eating frequency was significantly (P<0.05) lower in P0S70 compared to other treatmets. Eating time, however, did not differ (P>0,05) between treatments. Ruminating time increased (P<0,05) with increasing the proportion of banana pseudostem in the complete feed, but ruminating frequency did not differ between treatments (P>0,05). There was significant treatment effect (P<0,05) on resting time but not on resting frequency. It can be concluded that different ratio between gliricidia fallen leaf and banana pseudostem have significant effect on eating frequency, rumination time and resting time, but not on eating time, and the frequency of rumination and resting of Kacang goats.